2000
DOI: 10.1038/35018581
|View full text |Cite
|
Sign up to set email alerts
|

A chemokine-driven positive feedback loop organizes lymphoid follicles

Abstract: Lymphoid follicles are B-cell-rich compartments of lymphoid organs that function as sites of B-cell antigen encounter and differentiation. CXC chemokine receptor-5 (CXCR5) is required for B-cell migration to splenic follicles, but the requirements for homing to B-cell areas in lymph nodes remain to be defined. Here we show that lymph nodes contain two types of B-cell-rich compartment: follicles containing follicular dendritic cells, and areas lacking such cells. Using gene-targeted mice, we establish that B-ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
1,101
3
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,119 publications
(1,148 citation statements)
references
References 29 publications
39
1,101
3
5
Order By: Relevance
“…During a normal immune response, activated germinal center T-helper cells express high levels of CXCL13, which induces chemotaxis of cells with upregulated expression of the CXCL13 receptor CXCR5, including IgD-positive B cells and certain T-helper cell subsets. 7,13 This results in B cell entry into the follicle, as well as relocalization of unactivated germinal center T-helper cells and central memory T cells from the paracortex toward the follicles, where they can provide help to B cells during the process of antigen affinity maturation and isotype switching. CXCL13 also induces B cells to upregulate lymphotoxinalpha, which itself promotes CXCL13 expression in follicular dendritic cells, establishing a positive feedback loop thought to be critical in the organization of the lymphoid follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a normal immune response, activated germinal center T-helper cells express high levels of CXCL13, which induces chemotaxis of cells with upregulated expression of the CXCL13 receptor CXCR5, including IgD-positive B cells and certain T-helper cell subsets. 7,13 This results in B cell entry into the follicle, as well as relocalization of unactivated germinal center T-helper cells and central memory T cells from the paracortex toward the follicles, where they can provide help to B cells during the process of antigen affinity maturation and isotype switching. CXCL13 also induces B cells to upregulate lymphotoxinalpha, which itself promotes CXCL13 expression in follicular dendritic cells, establishing a positive feedback loop thought to be critical in the organization of the lymphoid follicle.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 The expression of CXCL13 by angioimmunoblastic T-cell lymphoma, as documented in our recent publication, 6 provides another piece of evidence linking the tumor cells to germinal center T-helper cells. CXCL13, a chemokine critical for B cell entry into germinal centers, 7 was identified by Kim et al 8 as one of the most highly upregulated genes in the germinal center T-helper cell subset. Kim et al also reported selective upregulation of several transcription factors in germinal center T-helper cells.…”
mentioning
confidence: 99%
“…Given that the early clustering of LTi cells within the embryo is dependent on CXCL13, and that CXCL13 is detected early in the developing lymph nodes of LT α ‐deficient mice,46, 47 this chemokine represents a key initiator of lymphoid organogenesis that functions upstream of LT β R signalling. At ELFs, CXCL13 and CCL21 regulate B‐cell and T‐cell infiltration and segregation at ELFs 48, 49, 50. Similarly, chemokines CCL19 and CXCL12 drive lymphocyte recruitment and the positioning of follicular DCs, B cells and plasma cells at germinal centres 48.…”
Section: Homeostatic Chemokines In Elf Developmentmentioning
confidence: 99%
“…4H and Table 1). In CXCR5-deficient mice, LTa is expressed but in the absence of the LTa/CXCL13 feedback-loop the level of LTa is not sufficient for normal development of follicular structures and differentiation of reticular cells into mature FDC [26,27]. Nonetheless, the CXCL13 1 stromal cells upregulate the FDC genes BP3, Enpp2 and Bgn (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4E and Table 1). These findings, summarized in Table 1, show the complexity of the development of the reticular cell network which supports the lymphoid structures.Transfer experiments showed that a crosstalk between CXCR5 1 B cells and CXCL13-secreting stromal cells is required for the upregulation of LTa and the development of mature FDC [26,27]. As a consequence, the level of LTa is not sufficient in CXCR5-deficient mice for the development of follicular structures.…”
mentioning
confidence: 99%